La gestión de calidad y su impacto competitivo en las pequeñas empresas lácteas del cantón Latacunga - Chiluisa Chasiluisa, Pricila Karolina (2017)
Nowadays, the companies in the dairy sector seek certification that demonstrates quality in their products. This is possible through the quality management adoption. Those are tools that help to achieve market competitiveness that is changing. The Ecuadorian customer is increasingly demanding in purchase terms and consumption of their products. They must guarantee the quality in the market. The companies must have some certification or be in the certifying process, that’s why it is necessary to implement the Quality management or have a system that can meet all the requirements and expectations to obtain a certification and ensure that the type of quality management can be adapted without any difficulty in the small dairy companies of Latacunga city. The inductive, qualitative and quantitative methods are applied in this research of the quality management currently at the Latacunga small companies began which have helped companies to lead the market to obtain profitability, competitiveness and productivity in such a way that contributes to meet the needs and requirements of the institution and the consumer. As a result, social impacts were obtained which contribute to have more advantages in the market and helping to carry each one its internal processes in an organized way closely related to the quality of dairy products. Finally, the benefits and the technical, social, economic and environmental character importance of a quality management certification are the contributions to the Latacunga small dairy companies is carried out a systematic, safe and guaranteed process of products with high standards affirmed to the customer that the company complies fully with all requirements under criteria that ensure and demonstrate the quality of the products that it consumes.